A Survey ofNFC Mobile Payment: Challenges and Solutions using Blockchain and Cryptocurrencies - Li, Dongcheng; Wong, W. Eric; Chau, Matthew; Pan, Sean; Koh, Liang Seng (2020 7th International Conference on Dependable Systems and Their Applications (DSA), 2020)
Near-field communication (NFC) is one of the essential technologies in the Internet of Things (IoT) that has facilitated mobile payment across different services. The technology has become increasingly popular, as cryptocurrencies like Bitcoin have revolutionized how payment systems can be designed. However, this technology is subject to security problems, such as man-in-the-middle attacks, doublespending, and replay attacks, raising the need to incorporate other solutions such as blockchain technology. Concerns about the security and privacy of payments using NFC technology raise the need to adopt blockchain-based cryptocurrency payment. For instance, NFC payment has been criticized for a lack of measures to counter potential attacks, such as brute force or double-spending. Thus, incorporating blockchain technology is expected to improve the security features of the NFC mobile payment protocol and improve user experience. Blockchain technology has been praised for enabling fair payment, as it permits direct transactions without engaging a third party. Therefore, integrating blockchain cryptocurrency in IoT devices will revolutionize the NFC payment method and provide value transfer using IoT devices. Combining NFC with blockchain technology and cryptocurrencies is necessary to address security and privacy problems. The purpose of this paper is to explore the potential behind incorporating blockchain technology and cryptocurrencies like Bitcoin in the NFC payment protocol.